Group divisible pentagon systems - Billington, Elizabeth J.; Hoffman D.G.; Maenhaut, Barbara M. (Utilitas Mathematica, 1999)
A group divisible pentagon system is a decomposition of the edge set of the λ-fold complete partite graph with m parts of size n into edge disjoint 5-cycles. In this paper it is shown that the obvious necessary conditions for such a decomposition are in fact sufficient.